The Efficacy of Low Dose Captopril Adjuvant for Natriuresis in Patient with Liver Cirrhosis with Ascites Who Have Received Furosemide and Spironolacton - Suyatmi Suyatmi; Bantar Suntoko; F. Sumanto; Hirlan Hirlan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2001)
Background: The ideal therapy for ascites in liver cirrhosis is a low sodium diet and a combination of furosemide and spironolacton. However, this still sometimes does not produce satisfactory Results, even after increasing the dose of the diuretic. Such failure occurs due to the influence of the Renin Angiotensin Aldosterone (RAA) system. Low doses of ACE inhibitors (captopril) should improve renal blood flow and increase filtration at the glomeruli, thus increasing natriuresis without causing haemodynamic imbalance. Study aim: To discover the natriuretic and diuretic effects of low dose captopril adjuvant in patients with liver cirrhosis who have received furosemide and spironolacton by measuring urinary sodium and 24-hour urine output. Materials and method: This study was conducted on in- and out- patients with liver cirrhosis and Ascites at the Dr. Kariadi Central Public Hospital, Semarang, who met the inclusion and exclusion criteria. The study took place from June 1st, 1997 to March 31st, 1998, and included 40 cases of liver cirrhosis with ascites. Study design: Open comparative randomized clinical trial with permuted blocks. All of the patients received a low fat diet, 40 mg of furosemide, 3x50 mg of spironolacton for 2 weeks, and patients with a urinary sodium level was below 80 mEq/L were randomized into two groups: group A receiving 3 x 6.25 mg of captopril, and group B receiving standard therapy.  Results:  Variable            Pre- treatment       Post – treatment      p  Group A : Urinary sodium level (meq/L)   65.450 ± 16.577       109.950 ± 49.109     0.001 24-hour urine output (cc)     1138.750 ± 480.438     1381.250 ± 394.441    0.004 Group B: Urinary sodium level (meq/L)  68.30 ± 12.85         91.750 ± 64.04      0.103 24-hour urine output (cc)       1390 ± 448.27        1392.50 ± 713.46     0.988   The pre- and post- treatment Results for Group A were significantly different. The pre- and post- treatment Results for Group B were not significantly different. Conclusion: Low dose (3 x 6.25 mg) captopril adjuvant in patients with liver cirrhosis and ascites who have received standard doses of furosemide and spironolacton could increase natriuresis and diuresis without causing haemodynamic imbalance.    Key words: Captopril, liver cirrhosis, ascites